PENGEMBANGAN MEDIA MOBILE LEARNING BERBASIS ANDROID DASAR PROGRAMMABLE LOGIC CONTROLLER PADA MATA PELAJARAN INSTALASI MOTOR LISTRIK SEBAGAI SUPLEMEN PEMBELAJARAN SISWA - Neni Astika; Muhammad Amin (Universitas Negeri Medan, 2022)
AbstractThe purpose of this study is to develop android-based Mobile learning media Basic Programmable Logic Controller in the Subject of Electric Motor Installation as a Learning Supplement for Class XI (TITL) Students of Sinar Husni Private Vocational School 2 TR Labuhan Deli using Adobe Flash CS6, validating android-based Mobile learning media. Basic Programmable Logic Controller in Electric Motor Installation Subjects as a Learning Supplement for Class XI (TITL) Students of Sinar Husni Private Vocational School 2 TR Labuhan Deli using Adobe Flash CS6. The research results are in the form of android-based mobile learning media development procedures that have been successfully compiled with the type of research and development or R&D using the ADDIE development model (analysis, design, development, implementation, evaluation). According to Sugiyono, the research and development steps are modified according to the author's needs with seven stages, namely: potential and problems, data collection, product design, design validation, design revsi, product trials, and product revisions. Media developed with adobe flash CS6 program and assisted with other programs kinemaster, the feasibility of android-based mobile learning media by material experts gets 85% with the category